Hepatoprotective Effect of Zingiber Officinale Roscoe against Anti-Tubercular Drug-Induced Liver Toxicity in Albino Rats - Babul Kumar (Journal of Global Pharma Technology, 2019)
The present study was aimed to investigate the hepatoprotective effect of ethanolic extract of Zingiber officinale Roscoe against hepatotoxicity induced by antitubercular drugs in Wistar albino rats. The ethanolic extract of rhizomes of Zingiber officinale was prepared using a Soxhlet apparatus. 24 Wistar albino rats were randomly divided into four groups (n=6). Except Group 1, all the other groups were treated with antitubercular drugs [isoniazid (I) (7.5mg/kg), rifampicin (R) (10mg/kg) and pyrazinamide (P) (35mg/kg)].  Group 2 and group 4 were treated with Silymarin (100mg/kg) and Zingiber officinale (500mg/kg) respectively, one-hour prior administration of antitubercular drugs for 30 days. At the end of the study, blood was collected and the two animals from each group were sacrificed and the liver was sent for histopathological examination. Data calculated by mean ± standard error of the mean and by unpaired t-test. Any p-value less than 0.05 have been considered as statistically significant. Antitubercular drugs significantly increased the Serum glutamate oxaloacetate transaminase (SGOT), Serum glutamate pyruvate transaminase (SGPT), Alkaline Phosphate (ALP), Total bilirubin (TB), unconjugated bilirubin (UB) and Total protein (TP) levels as compared to the control group. Treatment with Z. officinale extract (500mg/kg) significantly (P<0.05-P<0.001) reduces the antitubercular drugs induced hepatic toxicity and biochemical elevations towards normal. Zingiber officinale extract was hepatoprotective against antitubercular drugs induced hepatotoxicity in albino rats.Keywords:  Zingiber officinale extract, Isoniazid, Rifampicin, Pyrazinamide, Liver enzymes.